Intraoperative assessment of Baumann’s angle and carrying angles are very good prognostic predictors in the treatment of type III supracondylar humerus fractures in children - Ravi Kumar Biradar; Sharik Afsar Khan (Al Ameen Journal of Medical Sciences, 2017)
Background: In children supracondylar fracture of the humerus is one of the common fractures in first decade of life. Cubitus varus is the most common complication following supracondylar fractures in children irrespective of the method of treatment used. This study was conducted to establish the efficacy and the accuracy of intraoperative measurements of Baumann’s and carrying angles in the final outcome of supracondylar fracture humerus in children. Methods: Twenty eight cases of Gartland's Type III supracondylar humerus fractures were treated with closed reduction and percutaneous crossed Kirschner wire fixation under image intensifier. Intra operatively Baumann’s and carrying angles were measured and compared with the readings of the final follow up. The cases were followed up for an average period of 6 months. Results: The mean normal side Baumann's angle was 74.50 among boys and 73.40 among girls, the mean normal side carrying angle was 10.770 among boys and 14.30 among girls. The mean affected side Baumann's angle was 78.40 among boys and 79.10among girls; the mean affected side carrying angle was 8.770 among boys and 12.40 among girls at final follow up. There was no significant difference between the Baumann angle after reduction and that measured at follow-up. There was no case of cubitus varus deformity. Conclusion: Intraoperative assessment of Baumann’s angle and carrying angles are very good and reliable factors in the treatment of type III supracondylar humerus fractures in children.